Simple Chemical Solution Deposition of Co3O4 Thin Film Electrocatalyst for Oxygen Evolution Reaction - Jeon, Hyo Sang; Jee, Michael Shincheon; Kim, Haeri; Ahn, Su Jin; Hwang, Yun Jeong; Min, Byoung Koun (American Chemical Society, 2015)
Oxygen evolution reaction (OER) is the key reaction in electrochemical processes, such as water splitting, metal air batteries, and solar fuel production. Herein, we developed a facile chemical solution deposition method to prepare a highly active Co3O4 thin film electrode for OER, showing a low overpotential of 377 mV at 10 mA/cm(2) with good stability. An optimal loading of ethyl cellulose additive in a precursor solution was found to be essential for the morphology control and thus its electrocatalytic activity. Our results also show that the distribution of Co3O4 nanoparticle catalysts on the substrate is crucial in enhancing the inherent OER catalytic performance.
Keywords: WATER OXIDATION; COBALT-OXIDE; NANOWIRE ARRAYS; NI; CATALYST; PERFORMANCE; ELECTRODEPOSITION; REDUCTION; HYBRID